(untitled) (Damascus University Journal of Historical Studies, 2023)
During the 8th century AH/14th century AD, the Lusignan Kings in the Frankish Kingdom of Cyprus put all their energy into building a naval fleet for their kingdom in order to defend it against a potential Islamic attack after the conquest of the last Frankish settlement outpost in the Levant by the Mamluks in 689AH/1291AD, and in order to confront the growing Turkish piracy threat on the southern coasts of Asia Minor and the Aegean Sea, which had been causing a lot of damage and material losses to its trade. The arsenal of warships in the port of Famagusta was the main and only center to build the Kingdom’s war fleet, which enabled it to defend the island and impose its authority on a number of Turkish emirates and the important ports on the southern coast of Asia Minor during the 8th century AH/14th century AD, and to carry out acts of piracy, destructing ports, looting cities, and villages on the coasts of the Levant and Egypt, until the Kingdom’s fleet reached the peak of its power in the middle of the 8th century AH/14th century AD and dared to deal a severe blow to the Mamluk Sultanate during the reign of King Peter I of Lusignan, who carried out a crusade against Egypt and destroyed the important port of Alexandria. This was after the Lusignan Kings used the pretext of restoring the Holy Land as a cover for the Western forcers to obtain their support in fighting the Mamluks and blockading them economically, and thus shifting the routes of international trade between the East and the West to pass though their island across Asia Minor, and implementing their plan to maintain the prosperity of their trade.